2021
DOI: 10.3390/ijms22052486
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of blaCHDL Genes and Insertion Sequences Related to Carbapenem Resistance in Acinetobacter baumannii Clinical Strains Isolated in Warsaw, Poland

Abstract: Acinetobacter baumannii is an important cause of nosocomial infections worldwide. The elucidation of the carbapenem resistance mechanisms of hospital strains is necessary for the effective treatment and prevention of resistance gene transmission. The main mechanism of carbapenem resistance in A. baumannii is carbapenemases, whose expressions are affected by the presence of insertion sequences (ISs) upstream of blaCHDL genes. In this study, 61 imipenem-nonsusceptible A. baumannii isolates were characterized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…The most prevalent mechanisms of carbapenem resistance among A. baumannii isolates are CHDLs, with OXA-23 occurring the most often among A. baumannii worldwide [ 30 , 31 ]. Meanwhile, the results of our study showed that in our region, OXA-40-positive isolates are dominant, which is consistent with other studies conducted in Poland [ 32 ]. In our study, no isolates were simultaneously positive for both tested bla OXA genes.…”
Section: Discussionsupporting
confidence: 92%
“…The most prevalent mechanisms of carbapenem resistance among A. baumannii isolates are CHDLs, with OXA-23 occurring the most often among A. baumannii worldwide [ 30 , 31 ]. Meanwhile, the results of our study showed that in our region, OXA-40-positive isolates are dominant, which is consistent with other studies conducted in Poland [ 32 ]. In our study, no isolates were simultaneously positive for both tested bla OXA genes.…”
Section: Discussionsupporting
confidence: 92%
“…Only 1c and 2c displayed weak activity against Gram-negative rods with MICs ranging from 200 to >400 mg L −1 (Table S2.2†). Considering that resistance of Gram-negative rods is frequently associated with efflux pump activity, 41 we also determined the MICs of newly compounds in the presence of efflux pump inhibitor, i.e. , phenylalanine-arginine-β-naphthylamide (PAβN).…”
Section: Resultsmentioning
confidence: 99%
“…Besides intrinsic and mutational acquired resistance, the members of this bacterial species have acquired several β-lactamases and other ARGs by HGT [ 139 ]. Among them, and in addition to the intrinsic OXA-type β-lactamase, other OXA derivatives have been found [ 140 ], frequently linked to insertion sequences (ISs) located upstream the genes encoding β-lactamases [ 141 ]. Indeed, the activity of ISs, capable of modifying the expression of genes involved in resistance when located in the right positions, seems to be also instrumental for the acquisition of the resistance phenotype [ 142 , 143 ].…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%